Voltage Regulation of Boost Converter using Observer based Sliding Mode Controller - Ramadhani Kurniawan Subroto; Sapriesty Nainy Sari; Zainul Abidin; Kuo Lung Lian (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This study dealt with output voltage regulation of boost converter using observer based sliding mode controller comprises of adaptive PI sliding surface. Observer was designed to estimate the inductor current value, such that no sensor was required as a feedback. Adaptive PI sliding surface was constructed from the difference between estimated inductor current and its reference value. The stability of proposed method was ensured by using Lyapunov direct method. To test the system performance, numerical simulation was conducted. The result indicated that the integral absolute error value of proposed method was 0.19, which was 7 times less than sliding mode with PI sliding surface. Consequently, the proposed method was able to estimate accurately the inductor value, track the reference voltage perfectly, and show its robustness against parameter variations.